The propagation of aerosol perturbations in convective cloud microphysics - Heikenfeld, M; White, B; Labbouz, L; Stier, P (European Geosciences Union, 2018)
The impact of aerosols on ice- and mixed-phase processes in deep convective clouds remains highly uncertain and the wide range of interacting microphysical processes are still poorly understood. To understand these processes, we analyse diagnostic output of all individual microphysical process rates for two cloud microphysics schemes in the Weather and Research Forecasting model (WRF). We investigate the response of individual processes to changes in aerosol conditions and the propagation of perturbations through the microphysics all the way to the macrophysical development of the convective clouds. We perform simulations for two different cases of idealised supercells using two double-moment bulk microphysics schemes and a bin microphysics scheme. We use simulations with a comprehensive range of values for cloud droplet number concentration (CDNC) and cloud condensation nuclei (CCN) concentration as a proxy for aerosol effects on convective clouds. We have developed a new cloud tracking algorithm to analyse the morphology and time evolution of individually tracked convective cells in the simulations and their response to the aerosol perturbations. This analysis confirms an expected decrease in warm rain formation processes due to autoconversion and accretion for polluted conditions. The height at which the freezing occurs increases with increasing CDNC. However, there is no evidence of a significant increase in the total amount of latent heat release from freezing and riming. The cloud mass and the altitude of the cloud centre of gravity show contrasting responses to changes in proxies for aerosol number concentration between the different microphysics schemes.